2005
DOI: 10.1038/sj.jhh.1001877
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sibutramine in 2225 subjects with cardiovascular risk factors: short-term, open-label, observational study

Abstract: This study aims to determine the efficacy and tolerability of sibutramine hydrochloride in overweight and obese patients with cardiovascular risk factors. This was a 12-week, open-label, observational trial carried out in primary care settings. Patients' data were obtained from questionnaires received from 153 physicians. A total of 2225 overweight and obese (BMIX27 kg/m 2 ) patients received sibutramine in single daily doses of 10 and/or 15 mg. The study population included patients in general good health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…The associate director of the US Food and Drug Administration's Office of Drug Safety has indicated that sibutramine is one of five drugs currently on the market that may be endangering patients 41 . It was also reported that sibutramine is associated with QT prolongation and adverse cardiovascular effects, such as tachycardia, hypertension, and arrhythmia 40 , 42 , 43 . Recently it was revealed that sibutramine itself blocks hERG channels in a concentration‐, voltage‐, state‐, and time‐dependent manner 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The associate director of the US Food and Drug Administration's Office of Drug Safety has indicated that sibutramine is one of five drugs currently on the market that may be endangering patients 41 . It was also reported that sibutramine is associated with QT prolongation and adverse cardiovascular effects, such as tachycardia, hypertension, and arrhythmia 40 , 42 , 43 . Recently it was revealed that sibutramine itself blocks hERG channels in a concentration‐, voltage‐, state‐, and time‐dependent manner 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and tolerability of sibutramine (10-15 mg/day) in 2,225 overweight or obese patients with CVD risk factors were examined in a 12-week, open-label, observational trial carried out in primary care settings in Poland. [84] The study population included patients in general good health and with controlled hypertension (41%), T2DM (15%), hyperlipidaemia (45%), and who were chronic tobacco users (smokers) (37%). Mean systolic and diastolic BP and HR decreased from baseline to week 12.…”
Section: Safety Profile In Observational Studiesmentioning
confidence: 99%
“…In 3 months, 91% and 41% of subjects lost ≥ 5% and ≥ 10% weight from baseline, which was independent of the presence or absence of dyslipidemia. However, DM and hypertensive patients lost less weight comparatively, although BP and HR were decreased in all patients [76] . Meanwhile, sibutramine, when compared with placebo in a primary care setting followed for 54 weeks, showed more weight loss, which correlated with improvement in serum triglycerides and HDL-C levels.…”
Section: Effi Cacy and Safety Of Sibutramine In High-risk Patientsmentioning
confidence: 95%